Implementation of DCT Based Steganography Algorithm to Hide Information in Images - Septrian Napitupulu; Ryan Revaldo Siagian; Ramli Simanullang; Kelvin Daniel Manalu; Conglii Fao Silalahi (Journal Majelis Paspama, 2023)
Steganography is the art and science of hiding secret messages in digital media, ensuring that only the sender and intended recipient are aware of its existence. One of the widely used techniques in digital image steganography is the Discrete Cosine Transform (DCT) based method, which embeds secret data into the frequency domain of an image. This study explores the application of DCT-based steganography to hide information in an image while maintaining its visual integrity. The research methodology involves transforming the image into DCT coefficients, embedding the secret message into selected high-frequency coefficients, and then applying the Inverse Discrete Cosine Transform (IDCT) to reconstruct the stego image. The quality of the modified image is evaluated using the Peak Signal-to-Noise Ratio (PSNR) and Mean Square Error (MSE) metrics. The results show that the proposed method effectively hides information while maintaining image quality, as indicated by the high PSNR value and minimal MSE. This study contributes to the field of secure data communication by presenting a reliable and undetectable approach to information hiding.